Control of the topside Martian ionosphere by crustal magnetic fields. Issue 4 (14th April 2015) - Andrews, D. J.; Edberg, N. J. T.; Eriksson, A. I.; Gurnett, D. A.; Morgan, D.; Němec, F.; Opgenoorth, H. J.
Abstract We present observations from the Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) instrument onboard Mars Express of the thermal electron plasma density of the Martian ionosphere and investigate the extent to which it is influenced by the presence of Mars's remnant crustal magnetic fields. We use locally measured electron densities, derived when MARSIS is operating in active ionospheric sounding (AIS) mode, covering an altitude range from ∼300 km to ∼1200 km. We compare these measured densities to an empirical model of the dayside ionospheric plasma density in this diffusive transport‐dominated regime. We show that small spatial‐scale departures from the averaged values are strongly correlated with the pattern of the crustal fields. Persistently elevated densities are seen in regions of relatively stronger crustal fields across the whole altitude range. Comparing these results with measurements of the (scalar) magnetic field also obtained by MARSIS/AIS, we characterize the dayside strength of the draped magnetic fields in the same regions. Finally, we provide a revised empirical model of the plasma density in the Martian ionosphere, including parameterizations for both the crustal field‐dominated and draping‐dominated regimes.